2012
DOI: 10.1111/bjh.12118
|View full text |Cite
|
Sign up to set email alerts
|

Combination of recombinant factor VIIa and fibrinogen corrects clot formation in primary immune thrombocytopenia at very low platelet counts

Abstract: SummaryHaemostatic treatment modalities alternative to platelet transfusion are desirable to control serious acute bleeds in primary immune thrombocytopenia (ITP). This study challenged the hypothesis that recombinant activated factor VII (rFVIIa) combined with fibrinogen concentrate may correct whole blood (WB) clot formation in ITP. Blood from ITP patients (n = 12) was drawn into tubes containing 3Á2% citrate and corn trypsin inhibitor 18Á3 lg/ml. WB [mean platelet count 22 9 10 9 /l (range 0-42)]was spiked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The stabilization phase (MCF) was only influenced by fibrinogen. Similar additive effect has been previously shown ex vivo in post-cardiopulmonary bypass coagulopathy and in autoimmune thrombocytopenia [11,18].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The stabilization phase (MCF) was only influenced by fibrinogen. Similar additive effect has been previously shown ex vivo in post-cardiopulmonary bypass coagulopathy and in autoimmune thrombocytopenia [11,18].…”
Section: Discussionsupporting
confidence: 86%
“…Although its efficacy is not considered proven, the UKHCDO recommends the use of rFVIIa for postpartum bleeding in BSS [21]. Reports have also suggested a beneficial effect of fibrinogen supplementation in severe coagulopathies, even in the absence of hypofibrinogenemia [18,22] and, lately, also in immune thrombocytopenia [11]. To our knowledge no prior reports describe the use of fibrinogen supplementation alone or its administration together with rFVIIa in BSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCTs in ITP, haematological malignancy undergoing chemotherapy, MDS and liver disease Antifibrinolytics (Estcourt et al, 2016) In clinical use largely outside the setting of thrombocytopenia. Fibrinogen concentrate Larsen et al (2013) In clinical use largely outside the setting of thrombocytopenia. Several large ongoing RCTs at present.…”
Section: No Platelet Transfusionmentioning
confidence: 99%
“…In vitro work combining the administration of fibrinogen concentrate and rFVIIa demonstrated normalisation of whole blood clot formation in an in vitro model of ITP and suggested the two agents may have a synergistic effect (Larsen et al, 2013) and trials administering fibrinogen concentrate to thrombocytopenic pigs demonstrated an improvement in maximum clot firmness (Velik-Salchner et al, 2007). In vitro work combining the administration of fibrinogen concentrate and rFVIIa demonstrated normalisation of whole blood clot formation in an in vitro model of ITP and suggested the two agents may have a synergistic effect (Larsen et al, 2013) and trials administering fibrinogen concentrate to thrombocytopenic pigs demonstrated an improvement in maximum clot firmness (Velik-Salchner et al, 2007).…”
Section: Targeting Fibrinogenmentioning
confidence: 99%